Senior High School Students’ Collaborative Skills through Acid-Base Chemistry Practicum Activities - Shofrina Surya Dewi; Nurfina Aznam; Nur Inayah Amaliyah (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine collaboration skills profile of class 11 students at one of the public high schools in Paciran Regency. The reason for conducting this research is collaboration skills are one of the 21st century skills that must be mastered by students. The research conducted was descriptive quantitative with a cross-sectional survey method. The population of this study was 100 students. The sampling technique used purposive sampling technique with consideration from chemistry teachers. Collaboration skills are measured using an observation sheet containing statements according to aspects of collaboration skills. Data analysis techniques using MS Excel.  Collaboration skills aspect score data was analyzed quantitatively, then converted according to calculations into the very low, low, medium, good, and very good category. The student collaboration skills profile in this research includes 8 aspects are finding solutions, responsibility, mutual respect, interdependence, cooperation, communication, listening to other people's ideas, and commitment. In this research, it was found that the best aspect of collaboration skills in the very good category was the aspect of positive interdependence at 84.30%, cooperation at 88.50% and communication at 91.00%. The research results show that the average percentage of collaboration skills for all aspects is 83.50% and is in the good category.